Formulation and Optimization of Dicyclomine HCl mouth melt tablets by central composite design - E. Bhargav, C. Suryaprakash Reddy, M. V. Jyothi, T. Srikanth, S. Sravani, M. Suresh Krishna, T. Silpa, K. G. Murali, A. Sudha Rani (Journal of Applied Pharmaceutical Science, 2017)
Dicyclomine HCl mouth melt tablets were formulated and optimized by Central composite design. Method: Independent variables (concentrations of Dehydrated Banana powder DBP, X1 and Orange peel pectin powder OPP, X2) and dependent variables (In vitro dispersion time, Y1 and percentage drug release, Y2) were selected based on literature search. The model was found to be nonlinear and the curvature effect was significant. Therefore study resorted to composite design for optimization. Results: DSC studies indicated drug and excipients were compatible. Precompression parameters indicated fairly good flow properties. By direct compression method all the tablets were formulated, evaluated for postcompression parameters and were found to be within specified limits. Drug release from all the formulations followed first order. Contour plots were used to decide most economical batch which were in desired range. The statistical model is mathematically valid as the experimental values and predicted values were relatively close to each other and suggested that the statistical model is mathematically valid.Conclusion: The results demonstrated the effectiveness of the proposed design for development of Dicyclomine HCl Mouth melt tablets with optimized properties.
Keywords: Super disintegrants, Central composite design, Contour plots.